Competence of Quantitative Indicators of The Leading Clinical Signs of Cholestasis in Differentiation of its Grades - Khodiyeava Ozoda Ibragimovna (Universitas Muhammadiyah Sidoarjo, 2022)
The syndrome of intrahepatic cholestasis (SIC) is understood as a slowdown or cessation of bile secretion associated with changes either in its consistency (thickening) or in the lumen of the intrahepatic bile ducts (narrowing). Theoretically, any liver pathology can be complicated by the development of SIC, and only cases with a duration of more than 6 months are classified as chronic. Between the concepts of cholestasis and hepatic jaundice should not put an equal sign. For, the term cholestasis is a broader concept, and hepatic jaundice is just an integral part of it. Moreover, cholestasis can clinically occur with or without jaundice. It is clear that both forms of cholestasis, even within the same type of liver pathology, can manifest themselves in a different form of its severity.